Determination of Core–Shell Structures in Pd‐Hg Nanoparticles by STEM‐EDX1. Issue 22 (16th October 2015) - Deiana, Davide; Verdaguer‐Casadevall, Arnau; Malacrida, Paolo; Stephens, Ifan E. L.; Chorkendorff, Ib; Wagner, Jakob B.; Hansen, Thomas W.
Abstract: The structural and elemental configuration of a high‐performing Pd‐Hg electrocatalyst for oxygen reduction to hydrogen peroxide has been studied by means of high‐resolution scanning transmission electron microscopy. Pd‐Hg nanoparticles are shown to have a crystalline core–shell structure, with a Pd core and a Pd‐Hg ordered alloy shell. The ordered shell is responsible for the high oxygen reduction selectivity to H2 O2 . Abstract : The power of microscopy : The atomic structure of the alloyed Pd‐Hg alloy responsible for highly selective oxygen reductions reaction is studied by using high‐resolution scanning transmission electron microscopy (STEM). The alloy is found as a shell around Pd nanoparticles supported on carbon.